Tinjauan Hukum Islam terhadap Adat Memberi Hibah Pelumpat Dalam Pelangkahan Pernikahan - Abdul Aziz; Yono Yono; Sutisna Sutisna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
There are still many who follow traditions that are contrary to Islamic law, one of which happened in the Kayumanis Village, namely the custom of giving grants (money/goods) in the process of marriage. One of the reasons is that people still believe and believe in traditions that have been passed down, and are advice from parents that are impossible to violate. This study aims to find out what is the basis for the payment of fines/grants in this marriage step, what are the impacts for those who carry out the stepping-up custom in this marriage, and the relevance of this marriage-stepping custom to the legal rules of al'adat muhakkamah in Kayumanis Village, Tanah Sareal District. Bogor City. The method used in this study uses a qualitative method which is a method that focuses on in-depth observations. The results of this study are: what is the basis for community members who are still living this tradition that this tradition has become a tradition that is carried out from generation to generation. do not believe in this custom, just worried that their relationship is not good (between the brother and sister). Meanwhile, according to the view of Al'adat muhakkamah, the custom of giving this step cannot be used as evidence (proof, basis, or reason). This custom or tradition is very contradictory and not in line with Islamic law